The Face of Ecological Justice in The Justice System Anti Eco-Slapp in Indonesia - Sulis Setyowati (PT Inovasi Pratama Internasional, 2025)
Environmental activists, as leading activists in fighting for the right to a healthy and conducive environment, have faced criminalization efforts when fighting for environmental recovery due to the damage that has occurred. Environmental damage is caused by the mining sector which is the most dominant. Therefore, the integration of an ecologically just justice system will be realized by revitalizing Prosecutors and Judges in the Anti-Eco-SLAPP justice system. The role of Prosecutors will be in line with Justice for the Environment (JUST-E) because Prosecutors not only prioritize the legal-formal aspect, but also ensure that legal instruments are not used to silence environmental activists as environmental critics. Therefore, Prosecutors play a strategic role as supervisors and catalysts of ecological justice. JUST-E as a means of revitalizing the role of Prosecutors in handling Eco-SLAPP cases and judges implement preventive measures through interlocutory decisions and judge's decisions that implement the Anti-Eco-SLAPP mechanism.